2005
DOI: 10.1155/mi.2005.194
|View full text |Cite
|
Sign up to set email alerts
|

Serotonergic Mechanisms Influence the Response to Glucocorticoid Treatment in TMJ Arthritis

Abstract: The aims of this study were to investigate the influence of serotonin (5-HT) on the effects of intra-articular injections of glucocorticoid on pain of the temporomandibular joint (TMJ) in patients with inflammatory disorders of the TMJ. The pretreatment synovial fluid 5-HT was negatively, and plasma 5-HT positively, correlated to change in TMJ pain after treatment. The pretreatment plasma 5-HT was positively correlated to change in pressure-pain threshold after treatment. In conclusion, this study shows that l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 18 publications
2
13
0
2
Order By: Relevance
“…TMJ resting pain and tenderness to digital palpation decreased after intra-articular glucocorticoid treatment, which is in accordance with several previous studies [18–20]. In this study, the tenderness to digital palpation of the posterior aspect of the TMJ was negatively correlated to the level of thrombocyte particle concentration which in turn was associated with the inflammatory markers, erythrocyte sedimentation rate, and C-reactive protein.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…TMJ resting pain and tenderness to digital palpation decreased after intra-articular glucocorticoid treatment, which is in accordance with several previous studies [18–20]. In this study, the tenderness to digital palpation of the posterior aspect of the TMJ was negatively correlated to the level of thrombocyte particle concentration which in turn was associated with the inflammatory markers, erythrocyte sedimentation rate, and C-reactive protein.…”
Section: Discussionsupporting
confidence: 92%
“…There are reasons to consider pain on maximum mouth opening as intra-articular allodynia, which corroborates earlier findings [17]. It has previously been hypothesized that pressure-pain threshold and resting pain of the TMJ are modulated by different pain mechanisms [20], which is supported by the results of this study since there was no relation between these variables which responded differently to local administration of glucocorticoid. Future studies should investigate whether tenderness to digital palpation represents intra-articular pain or periarticular pain or both.…”
Section: Discussionsupporting
confidence: 91%
“…In TMD, elevated synovial 5-HT has been associated with increased pain, 81 and both local and systemic levels of 5-HT predict response to intra-articular glucocorticoid injection. 82 A small study found that the masseter muscles of women with myofascial TMD had more nerve fibers expressing 5-HT 3A receptors compared to healthy controls and that these fibers more frequently exhibited increased co-expression of 5-HT 3A receptors with Na v 1.8 channels, a marker of small, thinly myelinated nociceptive fibers. 83 A more recent study found no difference in plasma levels of 5-HT between patients with myofascial TMD and healthy controls but found that plasma dopamine levels were significantly increased in patients with TMD.…”
Section: Neuronal Signaling Molecules: Neurotransmitters and Neuropepmentioning
confidence: 99%
“…Zavisno od uzroka, pored ostale farmako i fizikalne terapije, KS imaju važnu ulogu u lečenju ovakvih stanja, jer smanjuju bolove, hipomobilnost TMZ i inflamaciju. Intrakapsularna injekcija KS može u velikoj meri olakšati simptome bolesti 26 . 15.…”
Section: Ramsay Hunt Sindrom (Rhs) Uzrokovan Je Reaktiviranjem Prethounclassified